2022
DOI: 10.4014/jmb.2210.10014
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Protein and Supplements on Sarcopenia in Human Clinical Studies: How Older Adults Should Consume Protein and Supplements

Abstract: Sarcopenia is a condition in which muscle mass, strength, and performance decrease with age. It is associated with chronic diseases such as diabetes, cardiovascular disease, and hypertension, and contributes to an increase in mortality. Because managing sarcopenia is critical for maintaining good health and quality of life for the elderly, the condition has sparked concern among many researchers. To counteract sarcopenia, intake of protein is an important factor, while a lack of either protein or vitamin D is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…However, recent review studies have indicated that protein supplementation alone may not lead to significant changes in parameters associated with sarcopenia [ 26 , 27 ], which contradicts the findings from previous studies [ 28 ]. On the other hand, a meta-analysis review has shown that exercise training alone or in combination with protein supplementation improved muscle mass, grip strength, reduced total fat mass, as well as waist circumference in individuals with sarcopenia [ 29 ].…”
Section: Introductionmentioning
confidence: 86%
“…However, recent review studies have indicated that protein supplementation alone may not lead to significant changes in parameters associated with sarcopenia [ 26 , 27 ], which contradicts the findings from previous studies [ 28 ]. On the other hand, a meta-analysis review has shown that exercise training alone or in combination with protein supplementation improved muscle mass, grip strength, reduced total fat mass, as well as waist circumference in individuals with sarcopenia [ 29 ].…”
Section: Introductionmentioning
confidence: 86%
“…The daily recommended protein intake for older adults is 1.2–1.5 g per kilogram of weight, which will ensure a positive nitrogen balance, improve protein synthesis, and potentiate the effects of training [ 19 , 20 ]. However, protein sources should be provided by food, since protein-based supplements have shown discrepancies in terms of results [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oral supplementation with protein, micronutrients, fat, or a combination thereof has demonstrated efficacy in enhancing muscle strength and physical performance in these individuals. 25,86 While vitamin D has received more attention in the context of bone health, the role of vitamin K, often overlooked, presents a potential link between COPD, osteoporosis, and sarcopenia, with associations noted in cross-sectional studies. 87 Muscle dysfunction and wasting stand out as prominent extra-pulmonary effects of COPD.…”
mentioning
confidence: 99%